2012
DOI: 10.1111/j.1398-9995.2012.02847.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE to recombinant allergens Api m 1, Ves v 1, and Ves v 5 distinguish double sensitization from crossreaction in venom allergy

Abstract: Specificity of sIgE to rSSMA of both species is excellent. Sensitivity of sIgE to rSSMA was optimal for wasp venom. Sensitivity of bee venom Api m 1 could be increased by adding rSSMA of other important bee venom allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 23 publications
4
97
3
3
Order By: Relevance
“…This most likely reflects difficulties in identification of the insects [18] as well as the fact that some of the reactions were not allergic ones. IgE to the major venom allergens rApi m 1, rVes v 1 and rVes v 5 have been shown to have a very high sensitivity and specificity when investigating DS patients [19,20,21,22]. Our study supports the value of adding IgE to major allergens in such patients, since double sensitization could only be confirmed in 10%.…”
Section: Discussionsupporting
confidence: 69%
“…This most likely reflects difficulties in identification of the insects [18] as well as the fact that some of the reactions were not allergic ones. IgE to the major venom allergens rApi m 1, rVes v 1 and rVes v 5 have been shown to have a very high sensitivity and specificity when investigating DS patients [19,20,21,22]. Our study supports the value of adding IgE to major allergens in such patients, since double sensitization could only be confirmed in 10%.…”
Section: Discussionsupporting
confidence: 69%
“…Only 47% of 76 patients with double positivity to whole bee and wasp (yellow jacket) venoms reacted to recombinant species-specific major allergens (rSSMA) from both of these species. The specificity of IgE to rSSMA was excellent, especially for wasp venom [31]. In another study, component-resolved diagnosis with wasp-specific recombinant allergen components Ves v I and Ves v 5 was a reliable method of diagnosing wasp/yellow jacket allergy [32].…”
Section: Triggers and Mechanismsmentioning
confidence: 99%
“…On the other hand, studies in patients allergic to bee venom demonstrated that phospholipase A 2 , phosphomonoesterase and hyaluronidase are the major allergens present in apitoxin (Müller et al, 2012). Thus, the removal of phospholipase A 2 and other high molecular weight proteins could improve the product safety and allow the treatment of many diseases at low risk.…”
Section: Introductionmentioning
confidence: 99%